2018
DOI: 10.1016/j.nicl.2018.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity derived thalamic segmentation in deep brain stimulation for tremor

Abstract: The ventral intermediate nucleus (VIM) of the thalamus is an established surgical target for stereotactic ablation and deep brain stimulation (DBS) in the treatment of tremor in Parkinson's disease (PD) and essential tremor (ET). It is centrally placed on a cerebello-thalamo-cortical network connecting the primary motor cortex, to the dentate nucleus of the contralateral cerebellum through the dentato-rubro-thalamic tract (DRT). The VIM is not readily visible on conventional MR imaging, so identifying the surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
205
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(218 citation statements)
references
References 107 publications
13
205
0
Order By: Relevance
“…Thalamotomy for tremor is aimed to impact on the anatomical connections within the cerebello‐thalamo‐cortical system, specifically the DRTT, stopping the tremor activity from propagating from the cerebellum to the motor cortex. Using tractography it is possible to define the anatomical boundaries of this tract (Akram et al, ; Meola, Yeh, Fellows‐Mayle, Weed, & Fernandez‐Miranda, ; Nowacki, Schlaier, Debove, & Pollo, ), and so the number of studies encouraging the tractography‐based segmentation of the DRTT for targeting in either thalamotomy or DBS is growing (Akram et al, ; Coenen et al, ; Sammartino et al, ; Tian et al, ; Tsolaki, Downes, Speier, Elias, & Pouratian, ). Our results are in line with these studies, and suggest that tractography based guidance during tcMRgFUS treatment strategy could be very beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Thalamotomy for tremor is aimed to impact on the anatomical connections within the cerebello‐thalamo‐cortical system, specifically the DRTT, stopping the tremor activity from propagating from the cerebellum to the motor cortex. Using tractography it is possible to define the anatomical boundaries of this tract (Akram et al, ; Meola, Yeh, Fellows‐Mayle, Weed, & Fernandez‐Miranda, ; Nowacki, Schlaier, Debove, & Pollo, ), and so the number of studies encouraging the tractography‐based segmentation of the DRTT for targeting in either thalamotomy or DBS is growing (Akram et al, ; Coenen et al, ; Sammartino et al, ; Tian et al, ; Tsolaki, Downes, Speier, Elias, & Pouratian, ). Our results are in line with these studies, and suggest that tractography based guidance during tcMRgFUS treatment strategy could be very beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…In a post‐hoc analysis of feasibility using probabilistic tractography to identify the Vim thalamus and DRTt, Akram and colleagues used graphical processing unit parallelization after obtaining preoperative high‐angular‐resolution diffusion imaging (HARDI) to segment the thalamus in 4 patients with tremor‐dominant PD and 5 patients with ET who underwent Vim DBS through indirect targeting. The elucidated segmented thalamic area had that the highest diffusion connectivity to the contralateral dentate nucleus and ipsilateral red nucleus and primary motor cortex was used to generate streamlines defining the DRTt.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in comparison to probabilistic tractography, streamlines created through deterministic means have not been found to be as reproducible when tracking through gray matter structures like the thalamus, as recently reported by Peterson and colleagues. 30 Probabilistic tractography using graphic processing unit parallelization can estimate up to three crossing fibers per voxel, thus they generate streamlines that can build a spatial connectivity distribution, a surrogate measure of anatomical connectivity 29,31 ; such resolution of crossing fibers can more realistically describe the DRTt.…”
Section: Limitationsmentioning
confidence: 99%
“…Resting-state functional MRI (rs-fMRI) is a suitable neuroimaging modality for the evaluation of many neurological and psychiatric diseases (Barkhof, Haller, & Rombouts, 2014;Hacker, Perlmutter, Criswell, Ances, & Snyder, 2012). To date, only a few studies have explored connectivity alterations in ET, and those that did were mainly focused on the cerebello-thalamo-cortical network, which is mainly related to motor symptoms (Buijink et al, 2015;Caligiuri et al, 2017;Mueller et al, 2017), or on the study of surgical therapeutic applications (Akram et al, 2018;Tuleasca et al, 2018). In a recent study, ET patients showed increased connectivity in resting-state networks involved in cognitive processes and decreased connectivity in the cerebellum and visual networks (Benito-León et al, 2015).…”
Section: Introductionmentioning
confidence: 99%